[OA083] Toward 4d micro-CT and radiotherapy of small animals using all-optical, ultrashort X-ray sources: feasibility study and preliminary experimental results. (August 2018) - Baffigi, F; Fulgentini, L; Gizzi, Leonida Antonio; Koester, P; Labate, Luca; Palla, D; Panetta, Daniele; Salvatori, P.A.; Pandola, Luciano; Pisciotta, Pietro; Russo, Giorgio; Mettivier, Giovanni; et al.
Abstract : Purpose: All-optical, laser-driven X/gamma-ray sources, based on the primary electron acceleration via the Laser WakeField Acceleration (LWFA) process, have now entered a mature phase in terms of beam parameters, shot-to-shot stability, and reliability, so as to be considered as promising tools in medical physics. The high electron acceleration gradient results in the possibility of accelerating electrons up to the 100s MeV range over very short distances and thus opening the way to the generation of high energy photons using "table-top" machines. The PRELUDE (PREclinical Laser-based Ultrafast Diagnostics and therapy) project is ongoing, as a collaboration among different Italian Institutions aimed at studying the application of a laser-driven X-ray source for 4D micro-CT and radiotherapy of small animals. Methods: As a first step, the exploitation of a Bremsstrahlung source driven by a LWFA, plasma-based accelerator is investigated, both theoretically and experimentally. The preliminary experimental results focused on characterizing the photon source, based on a 10TW ultrashort laser system for micro-CT of small animals is discussed. Issues related to both the primary electron acceleration and the generation of secondary photons via the Bremsstrahlung process will be discussed, including both numerical and experimental results. Results: The X-ray spectrum, beam intensity, e- contamination and photon dosimetry have been simulated using the GEANT4 toolkit on top of experimental measurements of the e- spectrum obtained using our setup and numerical estimations of the accelerated charge per pulse. Proof-of-principle radiographic images of physical phantoms obtained with photostimulable phosphor image plates are presented. Conclusions: We presented a system for small animal 4D-CT and radiotherapy based on a laser-driven X-ray source. The results of a theoretical and numerical study of a 4D micro-CT device based on a more advanced all-optical X-ray source based on Thomson scattering will be presented.